Seizure outcome-related factors in autoimmune encephalitis: A systematic review and meta-analysis - Luo, Peijuan; Zhong, Rui; Chen, Qingling; Lin, Weihong (Frontiers in Neurology, 2022)
Background Identifying the predictors for seizure outcome in autoimmune encephalitis (AE) and investigating how to prevent persistent seizures would have major clinical benefits effectively. Thus, we aimed to perform a systematic review and meta-analysis to examine seizure outcome-related factors in AE patients. Methods PubMed and EMBASE were systematically searched from inception to 10 June 2022 for studies investigating seizure outcome-related factors in AE. The pooled effect estimates, including standardized mean differences (SMDs) and odds ratios (ORs) with 95% confidence intervals (CIs), were calculated to estimate the effect of each included factor on the seizure outcome. Results A total of 10 studies were included in the meta-analysis. Our pooled results of this meta-analysis showed that five factors were found to increase the risk of persistent seizures in AE patients, including onset with seizures (OR = 2.106, 95% CI = 1.262–3.514, p = 0.004), status epilepticus (OR = 3.017, 95% CI = 1.995–4.563, p < 0.001), EEG abnormalities (OR = 1.581, 95% CI = 1.016–2.46, p = 0.042), MRI abnormalities (OR = 1.554, 95% CI = 1.044–2.283, p = 0.03), and longer time from clinical onset to immunotherapy (SMD = 1.887, 95% CI = 0.598–3.156, p = 0.004). Conclusion Our meta-analysis indicated that onset with seizures, status epilepticus, EEG abnormalities, MRI abnormalities, and longer time from clinical onset to immunotherapy were risk factors for persistent seizures in AE patients.